Laundry Management Information System Using Laravel Framework for Ema Laundry - Syukriyanto Latif; Camelia Praestuti; Letarius Tunjanan; Rahayu Septyaning Mistina (TEPIAN, 2026)
The rapid acceleration of small enterprise operations requires service sectors to transition from conventional management practices to high-efficiency computerized architecture. Ema Laundry encountered critical operational bottlenecks, including error-prone manual ledger entries, physical order tracking inefficiencies, and decentralized revenue recording which hampered business growth. This study addresses these challenges by implementing a secure, responsive, web-based laundry management information system designed to optimize micro-business transactional workflows. Developed utilizing the Laravel framework, a relational MySQL database, and Bootstrap components, the platform integrates automated computations to handle complex processing states and evaluate invoice calculations with high precision. The system engineering process undergoes systematic lifecycle validations, including rigorous data flow structural checks and comprehensive functional black-box evaluations to ensure stability under operational load. The implementation establishes clean data normalization patterns, eliminates tracking redundancies, and significantly improves service velocity. By providing a scalable digital transformation blueprint, this system contributes to the field of modern small business informatics, demonstrating that localized enterprise applications can be successfully modernized to enhance overall service delivery quality and administrative accountability. This research serves as a viable technical foundation for future integration with predictive behavioral analytics and broader service management ecosystems.